PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN DI CAFE HAMBAL AYO KOTA LUBUKLINGGAU - Fitria, Fitria; Azhar, Rudi; Supriyanto, Supriyanto; Nasruddin, Nasruddin; Naufal, Ghifandi (STKIP Persada Khatulistiwa Sintang, 2023)
The issue in this study is that the Hambalayo cafÃ© service is still subpar, and the food delivered does not always have a nice high quality taste. This is owing to a lack of employee dependability, which also has an impact on the food served. The purpose of this study is to ascertain the impact of service quality and facilities on customer satisfaction and loyalty at Cafe Hambalayo in Lubuklinggau City. The research method adopted is quantitative. The Likert scale is used as a measurement scale. With a sample of 100 respondents, the population in this study was Hambalayo cafe customers. Through the direct distribution of questionnaires, primary data was collected. Regression analysis, correlation coefficient, t test, coefficient of determination, and f test are among the data analysis techniques used. From this research, it can be concluded that: service quality influences customer satisfaction significantly; facilities influence customer quality significantly; service quality influences customer loyalty significantly; and facilities influence customer loyalty significantly. Customer happiness and loyalty are significantly impacted by the quality of service and facilities at Cafe Hambalayo in Lubuklinggau City